Pharmacophore Modeling, Docking, and Molecular Dynamics Simulation of Flavonoids as Inhibitors of Urokinase-type Plasminogen Activator - Bina Lohita Sari; Slamet Ibrahim; Daryono Hadi Tjahjono (Institute for Research and Community Services (LPPM) ITB, 2021)
The urokinase-type plasminogen activator (uPA) system plays a significant role in the invasion and metastasis of cancer cells. The present study was conducted to investigate natural product compounds as inhibitors and hit molecules of uPA using in-silico analysis. A pharmacophore model was built to screen the Indonesian Herbal Database (HerbalDB) to obtain inhibitors of different scaffolds. Based on the molecular docking score, four ligands were selected as potential uPA inhibitors. Subsequently, the stability of the ligand-uPA complex was analyzed using molecular dynamics (MD) simulation. An RMSD graph of the backbone protein and the RMSF values of the amino acid residues were also determined. In addition, the MM-PBSA method was applied to calculate the free binding energy. According to the results, Model_3, characterized by aromatic rings 23 (F1 and F2), cationic H-bond donor (F3), and metal ligator (F4) features, had an adequate goodness-of-hit score (GH). The four top-ranked ligands, isorhamnetin, rhamnetin, quercetin, and kaempferol, showed higher docking scores compared to the others. This study confirmed that isorhamnetin, rhamnetin, and kaempferol build stable complexes with uPA with lower binding energy than quercetin.